UGIJAR AND CANJAYAR NEOGENE BASINS (SE SPAIN): AN EXAMPLE OF STRIKE-SLIP BASIN EVOLUTION IN TRANSPRESSIVE REGIME (Rivista italiana di Paleontologia e Stratigrafia, 1990)
The present study has been carried out in the eastern part of the Alpujarran corridor (Betic Chain), an E-W trending basin, 80 km long, of Neogene-Quaternary age. In particular, the Ugijar and Canjayar basins (respectively named Basin 1 and Basin 2), controlled by an E-W trending left stepping right lateral strikeslip system, associated with NE-SW trending thrust faults, have been investigated. The stratigraphic sequence of the forementioned two basins, which can be up to 2000 m thick, is mainly due to tectonic subsidence and is here interpreted in terms of Sequence Stratigraphy. The age of the whole sequence, dated by means of planktonic foraminifera, is Late Serravallian-Pliocene.